A nitrogen-doped CoP nanoarray over 3D porous Co foam as an efficient bifunctional electrocatalyst for overall water splitting - Liu, Zong; Yu, Xu; Xue, Huaiguo; Feng, Ligang (Journal of materials chemistry. A, Materials for energy and sustainability, 2019)
An efficient and stable overall water splitting electrocatalyst is extremely crucial in hydrogen fuel generation. Herein, a nitrogen-doped CoP nanorod array over 3D porous Co foam (CoP-N/Co foam) is proposed as a bifunctional high-performance catalyst for the water splitting reaction. It can afford a current density of 50 mA cm −2 with an overpotential of 100 mV for the hydrogen evolution reaction and 260 mV for the oxygen evolution reaction; as a bifunctional catalyst for overall water-splitting, to reach a current density of 50 mA cm −2 , the CoP-N/Co foam|CoP-N/Co foam catalyst system requires a cell voltage of 1.61 V, significantly lower than the value of 1.78 V required for the RuO 2 /Co foam|Pt/C/Co foam electrode system assembled using the state-of-the-art commercial catalysts, and also outperforming most of the analogous catalysts reported recently. This electrolyzer can retain a current density of 50 mA cm −2 over 25 h of continuous operation without obvious performance degradation. Even under strongly corrosive and high oxidation potential conditions, the morphology and structure of the N-CoP nanorods strongly coupled with the Co foam were well retained after the electrocatalytic process. In order to deeply understand the catalytic contribution from doping and the morphology and support effects, Co foam, P-doped Co foam, CoP/Co foam and CoP-N/Co foam as catalysts were comparatively evaluated by spectroscopic and electrochemical techniques. It is found that simple doping of non-metallic nitrogen into CoP can greatly increase its catalytic activity, stability, kinetics and catalytic efficiency for water splitting both in the anode and cathode reaction. The present work provides an efficient approach for performance enhancements of metal phosphide catalysts and a promising electrode for energy-efficient water electrolysis. A nitrogen-doped CoP nanoarray over 3D porous Co foam is proposed as a robust bifunctional catalyst for the hydrogen evolution reaction and oxygen evolution reaction in the overall water-splitting reaction.